Sinergi Tasawuf dalam Menggapai Kebahagiaan Serta Pengaruhnya pada Semangat Belajar Anak - Wahidah, Jumaiyah Nur; Khodijah, Khodijah (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
The spirit of learning is a drive or enthusiasm shown by students through their involvement in learning to acquire skills and knowledge. The spirit of learning can affect the learning outcomes that students achieve. This study aims to describe the influence of the synergy of Sufism in increasing happiness that can affect the enthusiasm for learning, this study uses a library method in obtaining data that will be presented and the results obtained are that the synergy between the teachings of Sufism and efforts to achieve happiness have a significant influence on a person's enthusiasm for learning. Sufism practices such as muhasabah, zuhud, and tawakkal can create a calm, hopeful, and goal-oriented inner condition. This positive inner condition, in turn, encourages individuals to be more active in seeking knowledge. The synergy between Sufism and efforts to achieve happiness is the key to increasing the enthusiasm for learning. By understanding and practicing the values ??of Sufism, individuals can find strong intrinsic motivation to continue learning and developing.